DOI: 10.20868/upm.thesis.57357
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and mechanisms of insecticide resistance in Ceratitis capitata and its implications for resistance management

Abstract: Chapter 2. Functional characterization and fitness cost of spinosad resistant alleles in Ceratitis capitata…..33 2.1. Rationale for the study…..35 2.2. Materials and methods…..36 2.2.1. C. capitata strains and generation of isolines…..36 2.2.2. Genomic DNA extraction, PCR of intronic/exonic boundaries and sequencing of Ccα6…..40 2.2.3. RNA extraction, RT-PCR, qPCR of Ccα6 exons, PCR and sequencing of codifying regions…..40 2.2.4. GAL4>UAS targeted expression of Ccα6 isoforms in D. melanogaster…..42 2.2.4.1. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 188 publications
(378 reference statements)
0
4
0
Order By: Relevance
“…A recent study did not reveal significant levels of resistance of field populations to deltamethrin and spinosad in Greece. 12 However, Guillem-Amat (2019) 18 reported that Mag-netMed traps coated with deltamethrin do not provide a complete control for all Spanish field populations tested. Altogether, IRM strategies aimed to overcoming resistance to lambdacyhalothrin and preventing the development of resistance to spinosad and deltamethrin are required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study did not reveal significant levels of resistance of field populations to deltamethrin and spinosad in Greece. 12 However, Guillem-Amat (2019) 18 reported that Mag-netMed traps coated with deltamethrin do not provide a complete control for all Spanish field populations tested. Altogether, IRM strategies aimed to overcoming resistance to lambdacyhalothrin and preventing the development of resistance to spinosad and deltamethrin are required.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of cross‐resistance between lambda‐cyhalothrin and deltamethrin (MO1), as observed for the resistant laboratory strain W‐1Kλ 6 . In this case, the expected mortality for SS individuals would be s ( d ) SS = 0.9, as it was observed that not all the individuals from the susceptible laboratory strain C reach the traps and die 18 . The absence of cross‐resistance between lambda‐cyhalothrin and deltamethrin in field populations (MO2), in which all the genotypes would be expected to be as sensitive as C strain ( s ( d ) SS = s ( d ) RR = s ( d ) SR = 0.9).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations